Numerical investigation of vortex shedding mechanism for staggered rows of cylinders - Ghazala Nazeer; Shams-Ul Islam; Sehrish Hassan Shigri (Heliyon, 2019)
This numerical investigation deals with study of flow past seven square cylinders arranged in staggered configuration. Simulations to the underlying problem are carried out by using the single relaxation time lattice Boltzmann method. The gap spacing between the staggered rows is varied in streamwise direction from 0.25 to 2 and for three transverse spacing i.e. T* = 1, 1.5 and 2. The complex vortex shedding mechanism is visualized for different streamwise and transverse gap spacings. Furthermore, the vortex shedding mechanisms in the wake of downstream row of cylinders are debated by using vorticity snapshots, time-trace plots of drag and lift coefficients and power spectra visualization of lift coefficient. It is also observed that the secondary cylinder interaction frequency contributes significantly to the hydrodynamic forces experienced by the cylinders. The physical parameters, such as Strouhal number, the drag and lift coefficients and their root-mean-square values have also been discussed in detail.